(untitled) (Fractal: Journal of Psychology, 2009)
This study discuss how the concept of Meaning allowed Lacan to reconduct the analytical praxys. Appealing to works of Lacan and commentators, the concept of meaning will be investigated in its double aspect, the critic one - as means to fight the claims of naturalization of the psyche; and the postulated one - as responsible for the settlement of intersubjectivity as a fundamental dimension to capture the clinical experience. Although assuming that Lacan later abandoned intersubjectivity, the article examines the legacy of the theory of "Meaning" in psychoanalysis. Its main contribution would have been the fight against the naturalization of the subject.